2018
DOI: 10.21608/ajs.2018.28384
|View full text |Cite
|
Sign up to set email alerts
|

IDENTIFICATION AND CHARACTERIZATION OF HEAT SHOCK PROTEINS IN FOUR EGYPTIAN MAIZE INBRED LINES (Zea mays L.)

Abstract: The heat shock protein (HSP) family is one of the proteins universally accumulated under heat stress condition. Four Egyptian maize inbred lines (Zea mays L.) were studied to identify heat shock proteins under heat stress at 45°C as protein markers for detecting the thermo-tolerance inbreds. The protein fingerprints of four inbred lines were performed by grain total-soluble protein electcophoretic analysis. The protein electrophoretic analysis showed 18 bands in a distinct pattern of K1 and K7 inbred lines, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Plant materials: Two Egyptian inbred lines of maize (Zea mays L.) K1 and K7 were used in this study. The two lines K1 and K7 were chosen because they showed a high number of HSP bands after exposure to heat stress at 45EC as compared to other maize lines in a previous study 28 and the proteomic analysis for the HSPs manifested five spots were induced after heat treatment at 45EC 29 . Also, high expression levels of HSP genes in these two lines were detected by using western blot and real-time Polymerase Chain Reaction (PCR) methods 30 .…”
Section: Study Areamentioning
confidence: 99%
“…Plant materials: Two Egyptian inbred lines of maize (Zea mays L.) K1 and K7 were used in this study. The two lines K1 and K7 were chosen because they showed a high number of HSP bands after exposure to heat stress at 45EC as compared to other maize lines in a previous study 28 and the proteomic analysis for the HSPs manifested five spots were induced after heat treatment at 45EC 29 . Also, high expression levels of HSP genes in these two lines were detected by using western blot and real-time Polymerase Chain Reaction (PCR) methods 30 .…”
Section: Study Areamentioning
confidence: 99%
“…An Egyptian inbred line of maize (Zea mays L.) "K1" was used in this study which was developed by the plant breeding group, Genetic and Cytology Department, National Research Centre, Giza, Egypt. The inbred "K1" is one of four Egyptian maize inbred lines (Zea mays L.) that were studied to identify heat shock proteins under heat stress at 45°C as protein markers for detecting the thermo-tolerance inbred lines, which showed four bands of heat shock proteins with molecular weights of 82, 22, 17, and 10 kDa after exposing to 45°C for 2 and 4 h which may be an indication of thermo-tolerance (Mahmoud et al 2018).…”
Section: Methodsmentioning
confidence: 99%
“…The four lines were previously studied to identify HSPs under HS at 45°C as protein markers for detecting the thermo-tolerance lines. The results indicated that the three lines K1, K7 and G342 are tolerant and the line Rg59 is susceptible (Mahmoud et al, 2018).…”
Section: Plant Materialsmentioning
confidence: 97%